PENGARUH UMUR PEMANGKASAN PUCUK DAUN DAN PEMBERIAN PUPUK KANDANG AYAM TERHADAP PRODUKSI TANAMAN MENTIMUN (Cacumis sativus L.) - Sitinjak, Lentina; Harefa, Kurnia Selekta Etika (AGROSUSTAIN, 2023)
One of the ways to increase cucumber production is through intensive cultivation techniques with a shoot pruning system and the application of organic fertilizers. The focus of this research is to optimize fruit quality and quantity. This research was conducted at Jalan Anggrek II Simpang Selayang, Medan Tuntungan District, Medan City, North Sumatra, starting in December 2023 until February 2024, using a Randomized Group Design (RAK) consisting of two factors. Parameters observed in this study were the number of fruits per plant, weight per fruit, fruit weight per plant, fruit diameter and fruit length. Based on the results of the study, it can be concluded that pruning shoots at the age of 29 days after planting significantly increases the number of fruits per plant, weight per fruit, fruit weight per plant, fruit diameter and fruit length. Doses of chicken manure significantly increased the number of fruits per plant, weight per fruit, fruit weight per plant, fruit diameter and fruit length. The interaction between shoot pruning and manure dose had no significant effect on all parameters observed. Pruning shoots at the age of 29 days after planting increased the number of fruits per fruit by 9.06%, increased fruit weight per plant by 19.78%, increased fruit weight per plot by 28.35%.